SOCIAL NETWORKS AS A COMPONENT OF EDUCATIONAL AREA OF THE HIGH SCHOOL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Currently, there is an active process of expanding the educational space, including the higher education of the Russian Federation, at the expense of informatization. Informatization of educational area of higher education is impossible without using web-technologies and, such as social networks. The authors of the article suggest social networks to be understood as a working version of an “interactive multi-user website that implements a network social structure consisting of a group of nodes — social objects (groups of people, communities) and links between them (social relationships), on the basis of which participants can establish relationship with each other. Currently, there are several main functions of social networks: educational; adaptive (acts as a resource of adaptation); compensatory (replacing institutional mechanisms of adaptation); informational (supports communication between authors of social interaction); transit (allows an individual to make the transition along the social ladder); coordination; social support functions (strengthen communication within and outside the network) and the function of a sociocultural marker. Social networks, speaking as a special social space of the Internet, have become the sphere in which traditional forms of socialization and social relations are transformed, and communication as a type of leisure activity becomes possible not in the traditional form of direct live communication, but acquires the features of simple communication. The authors state that at present using social networks in the educational area of the higher school of the Russian Federation is minimal. The network educational community on the basis of a social network - a virtual educational environment - is necessary, first of all, for students who have difficulties in communicating directly or need additional knowledge and skills that an educational institution cannot provide. From the point of view of education, social networks can be: freely available (non-specialized networks for which professional communities are not paramount and purely professional communities of practice) and in a corporate format (free-access networks; not specialized (“general profile” network)). The advent of Web 2.0 has expanded the possibilities of using social networks in education, has changed the attitude to the Internet as a whole, and teachers have begun to more actively use the Internet services for educational and educational purposes, in extracurricular activities and creative activities. It has already been experimentally proven that network communities can serve as pedagogical practices for development: co-thinking, tolerance, mastering decentralized models, critical thinking.